Treatment of Idiopathic Persistent Hiccups with Positive Pressure Ventilation -A Case Report- - Byun, Sung Hye (The Korean Pain Society, 2012)
A 41-year-old male patient presented with idiopathic persistent hiccups. The hiccups did not respond to pharmacologic treatments including cisapride, omeprazole, and baclofen. Phrenic nerve block was also ineffective. However, the persistent hiccups were successfully treated with short-term positive pressure ventilation using a short-acting muscle relaxant.